2007
DOI: 10.1177/0146167207310457
|View full text |Cite
|
Sign up to set email alerts
|

Victoria's Dirty Secret: How Sociocultural Norms Influence Adolescent Girls and Women

Abstract: The present studies tested whether the salience of sociocultural norms for ideal appearance leads women to base their self-worth more strongly on appearance, which in turn leads them to feel more concerned with others' perceptions and less satisfied with their bodies. Study 1 tested this model by manipulating the salience of the sociocultural norm among female university students. The model was supported. In Study 2 an intervention challenging the legitimacy of the sociocultural norm was delivered to female an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
42
1
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 41 publications
3
42
1
1
Order By: Relevance
“…We take the position that the role of 11 contingencies that are specific to appearance should be more closely associated with body 12 appearance concerns and unhealthy weight control behaviors than general external 13 contingencies. Our position echoes that of Strahan et al (2008) who similarly argued that 14 research examining the impact of socio-cultural norms for appearance on body image-related 15 outcomes should focus on appearance-related contingencies. This argument is conceptually 16 grounded in that success and failure in personally valued domains are more likely to influence 17 self-worth than outcomes in domains that are less pertinent to the individual (Kernis, 2003).…”
supporting
confidence: 55%
“…We take the position that the role of 11 contingencies that are specific to appearance should be more closely associated with body 12 appearance concerns and unhealthy weight control behaviors than general external 13 contingencies. Our position echoes that of Strahan et al (2008) who similarly argued that 14 research examining the impact of socio-cultural norms for appearance on body image-related 15 outcomes should focus on appearance-related contingencies. This argument is conceptually 16 grounded in that success and failure in personally valued domains are more likely to influence 17 self-worth than outcomes in domains that are less pertinent to the individual (Kernis, 2003).…”
supporting
confidence: 55%
“…Furthermore, there is emerging research suggesting alternative norms for female body 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 61 62 63 64 65 Gender Comparisons 6 image. Women in today's society must choose between acknowledging personal shortcomings against societal beauty standards, or risking social rejection by abandoning the beauty ideal in an effort to be unique and to gain independence (Strahan et al, 2008). Through the use of hypothetical conversations, Tompkins, Martz, Rocheleau, and Bazzini (2009) found that female participants appreciated a target woman's self-accepting body talk more than fat talk in a vignette about body image, suggesting an alternative norm of body acceptance that competes with the known fat talk norm in the US.…”
mentioning
confidence: 99%
“…13 It has be en ar gu ed that thin in ter na li za ti on is a risk factor for ea ting di sor ders and wo men who in ter na lize the se stan dards ha ve lo wer body sa tis fac ti on af ter ex po su re to thin me di a ima ges. In ad di ti on, ac cor ding to Dit marr and Ho ward, 14 thin ness-based so ci al com pa ri son with me di a mo dels is li kely to de pend on wo men's in ter na li za ti on-whet her or not they en dor se thin ness as a per so nal ide al.…”
Section: Ma a T Te E R Ri I A Al L A An Nd D M Me Et T H Ho Od Ds S:mentioning
confidence: 99%
“…So me stu di es fo und that ex posu re to thin me di a ima ges may ha ve a det ri men tal ef fect on adult and ado les cent fe ma les' body ima ge sa tis fac ti on and re la ted af fec ti ve sta tes and be ha vio ral dis po si ti ons. 13,[15][16][17][18][19][20] Ot her stu di es, ho we ver, have fo und litt le or no ef fect of thin me di a ima ges on fe ma les' body ima ge sa tis fac ti on. 21,22 Ac cor ding to Dal ley et al 23 the im pact of ex posu re to thin me di a ima ges ap pe ars to vary as a re sult of in di vi du al dif fe ren ces.…”
Section: Ma a T Te E R Ri I A Al L A An Nd D M Me Et T H Ho Od Ds S:unclassified